COBIT 2019 Implementation for Enhancing IT Governance in Educational Institutions - Gilberth Wattimury; Ahmad Faza (JISKA (Jurnal Informatika Sunan Kalijaga), 2023)
This study explores the application of COBIT 2019 in assessing IT governance at Yayasan Bunda Hati Kudus, a prominent educational institution. The research uses the Planning, Field Work, Reporting, and Follow-Up stages to leverage the Gallegos' framework. Findings reveal that Yayasan Bunda Hati Kudus operates at IT governance level two, employing COBIT 2019 domains BAI04, BAI05, and BAI11. Notably, the organization faces challenges in implementing IT across campuses, requiring remedies for decentralized systems, operational disruptions, and unmet needs. The study underscores COBIT's efficacy in addressing IT-related challenges and governance implementation. The novelty lies in adapting COBIT 2019 to assess IT governance within an educational context, offering tailored insights for enhancing capability levels and aligning IT strategies with organizational priorities.